Fructan‐sensitive children with irritable bowel syndrome have distinct gut microbiome signatures. Issue 4 (13th December 2020) - Chumpitazi, Bruno P.; Hoffman, Kristi L.; Smith, Daniel P.; McMeans, Ann R.; Musaad, Salma; Versalovic, James; Petrosino, Joseph F.; Shulman, Robert J.
Summary: Background: Dietary fructans may worsen gastrointestinal symptoms in children with irritable bowel syndrome (IBS). Aim: To determine whether gut microbiome composition and function are associated with childhood IBS fructan‐induced symptoms. Methods: Faecal samples were collected from 38 children aged 7‐17 years with paediatric Rome III IBS, who previously completied a double‐blind, randomised, placebo‐controlled crossover (fructan vs maltodextrin) trial. Fructan sensitivity was defined as an increase of ≥30% in abdominal pain frequency during the fructan diet. Gut microbial composition was determined via 16Sv4 rDNA sequencing. LEfSe evaluated taxonomic composition differences. Tax4Fun2 predicted microbial fructan metabolic pathways. Results: At baseline, 17 fructan‐sensitive (vs 21 fructan‐tolerant) subjects had lower alpha diversity ( q  < 0.05) and were enriched in the genus Holdermania . In contrast, fructan‐tolerant subjects were enriched in 14 genera from the class Clostridia. During the fructan diet, fructan‐sensitive (vs tolerant) subjects were enriched in both Agathobacter ( P  = 0.02) and Cyanobacteria ( P  = 0.0001). In contrast, fructan‐tolerant subjects were enriched in three genera from the Clostridia class. Comparing the fructan vs maltodextrin diet, fructan‐sensitive subjects had a significantly increased relative abundance of Bifidobacterium ( P  = 0.02) while fructan‐tolerant subjects had increased Anaerostipes ( P  = 0.03) during the fructan diet. Only fructan‐sensitive subjects had a trend towards increased predicted β‐fructofuranosidase during the fructan vs maltodextrin diet. Conclusions: Fructan‐sensitive children with IBS have distinct gut microbiome signatures. These microbiome signatures differ both at baseline and in response to a fructan challenge.